Safety and immunogenicity of an adjuvanted Escherichia coli adhesin vaccine in healthy women with and without histories of recurrent urinary tract infections: results from a first-in-human phase 1 study - Gary R. Eldridge; Heidi Hughey; Lois Rosenberger; Steven M. Martin; Andrew Marc Shapiro; Elizabeth D'Antonio; Kent G. Krejci; Neal Shore; James Peterson; Andrea S. Lukes; Courtney M. Starks (Taylor & Francis Group, 2021)
Antibiotic resistance among gram-negative bacteria continues to rise globally at an alarming rate. New vaccines that prevent bacterial infections and reduce antibiotic use could provide a potential solution to these problems. This study focused on development of an investigational vaccine to prevent recurrent urinary traction infections (UTI) caused by gram-negative bacteria that use type 1 pili to adhere to, invade, and colonize human bladders. The vaccine antigen is FimH, an adhesin protein on the tip of type 1 pili with a lectin binding domain that enables attachment to glycoproteins on mammalian bladders. This was a phase 1, open-label, dose escalation study evaluating the vaccine in 67 healthy women with and without histories of recurrent UTI. The objectives of the study were to evaluate the safety, tolerability, and immunogenicity of different dosages of the antigen and adjuvant of the vaccine. All dosages were well-tolerated and a low incidence of systemic reactions occurred. No serious adverse events related to the vaccine were reported. The vaccine induced both binding and functional antibodies. The women with histories of recurrent UTI demonstrated greater than 150-fold increases in antibodies against the N-terminal region of FimH. Based on the results of this phase 1 study, this vaccine is proceeding to a double-blind, randomized, placebo-controlled phase 2 study. If this vaccine is successful in future studies, it could potentially prevent millions of recurrent UTI globally and reduce the development of antibiotic resistance.